Porous silicon filled with Pd/WO3–ZnO composite thin film for enhanced H2 gas-sensing performance. Issue 63 (14th August 2017) - Kumar, Arvind; Sanger, Amit; Kumar, Ashwani; Chandra, Ramesh
Abstract : FESEM surface morphology and the schematic view of the Pd/WO3 –ZnO composite sensor with Ag paste contacts. Abstract : Here, pure ZnO, WO3 and Pd/WO3 –ZnO composite porous thin films were successfully synthesized directly on porous silicon by a reactive DC magnetron sputtering technique. A sensor based on the Pd/WO3 –ZnO composite porous thin films showed remarkably improved H2 sensing performance with good stability and excellent selectivity compared to that of pure WO3 and ZnO, at a relatively lower operating temperature (200 °C) and with a low detection range of 10–1000 ppm. The enhanced response can be attributed to the heterojunction formed between two dissimilar materials. The underlying mechanism behind their good performance for H2 gas was discussed in detail.